Proposed Waqf framework for food security and price stabilization policy of rice in Indonesia - Alif Wildana, Muhammad Dandy; Syed Jaafar Alhabshi, Syed Musa (IIUM Press, 2018)
This paper provides a framework for agriculture waqf in support of a food security strategy and price stabilization policy for rice in Indonesia. Instability and inefficiency of rice production has increased, involving a high cost of production and low access of financing, which leads to instability of stock. Long supply chains, mismatch of supply and demand of rice due to the timing gap between harvesting periods, also encourages speculative practices. Waqf, through agricultural ventures that focus on producing rice, can play multiple roles and provide solutions for the entire supply chain of rice involving a framework designed to address the problems of rice in Indonesia. The proposed framework is intended to benefit all related stakeholders by maximizing the potential of waqf assets that already exist in Indonesia, with the justification based on the data, that provides an insight in to the real conditions of rice in Indonesia. The findings reveal that waqf can fit perfectly in the current framework for food security and price stabilization policy, with an additional reserve that independently enables the custodian of waqf assets from agriculture (rice) ventures. This promotes farmers as waqf partners, to create a stable rice production environment and to shorten long supply chain by creating associated commercial subdivisions. Hence the benefit is distributed to both farmers and customers through various subsidies and necessary aid in order to attain food security and stabilize the price of rice thereby improving the welfare of Indonesians